Проблема перевода безэквивалентной лексики на материале сказки П. Ершова «Конёк-горбунок» - Баранова, И.С.; Лукинова, М.Ю. (Культура народов Причерноморья, 2013)
В даній статті буде досліджена проблема перекладу безеквівалентної лексики з російської
мови на англійську та українську мови. Безеквівалентна лексика досить часто викликає труднощі в
процесі перекладу, вимагаючи не просто знання мови, але й знання культури, до якої даний мова
належить. У будь-якій мові є слова, що не мають однослівної перекладу в інших мовах. Для ілюстрації
даної проблеми були взяті приклади з казки П. Єршова «Коник-Горбоконик».
Ключові слова: безеквівалентна лексика, реалія, культура, переклад В данной статье будет исследована проблема перевода безэквивалентной лексики с
русского языка на английский и украинский языки. Безэквивалентная лексика довольно часто вызывает
трудности в процессе перевода, требуя не просто знания языка, но и знания культуры, к которой
данный язык относится. В любом языке есть слова, не имеющие однословного перевода в других языках.
Для иллюстрации данной проблемы были взяты примеры из сказки П. Ершова «Конёк-горбунок».
Ключевые слова: безэквивалентная лексика, реалия, культура, перевод This paper studies the translation challenges caused by nonequivalent vocabulary from Russian into
English and Ukrainian languages. Nonequivalent vocabulary often causes problems in the translation process,
requiring not only language skills, but also knowledge of the culture to which the language belongs. In every
language there are words that do not have single-word translation in other languages.
According to theoretical studies major challenges in translation of nonequivalent vocabulary are the following
two:
1) lack of an equivalent in the target language because of the lack of the mentioned phenomena and the
corresponding lexical unit of the subject ;
2) the need, along with the objective meaning of the word, to give it extra coloring.
Summarizing the existing theoretical literature, we can say that the most typical ways to translate nonequivalent
vocabulary are transcription and transliteration, loans, descriptive translation, neologisms creation,
approximate translation and functional analogue.
The choice of methods of translation of nonequivalent vocabulary is influenced by genre characteristics of text.
Another factor, identifying the translation method is its significance in the context. This is especially true in fairy
tales, considering the cultural, national, and value of this specific genre, its educational focus and target
audience.To illustrate this problem, samples were taken from a fairy tale "Humpbacked Horse" by P. Ershov.
Key words: nonequivalent vocabulary, realia, culture, translation